Positron Emission Tomography Detects In Vivo Expression of Disialoganglioside GD2 in Mouse Models of Primary and Metastatic Osteosarcoma - Butch, Elizabeth R.; Mead, Paul E.; Amador Diaz, Victor; Tillman, Heather; Stewart, Elizabeth; Mishra, Jitendra K.; Kim, Jieun; Bahrami, Armita; Dearling, Jason L.J.; Packard, Alan B.; Stoddard, Shana V.; Vāvere, Amy L.; et al. (Cancer research (Chicago, Ill.), 2019)
The cell membrane glycolipid GD2 is expressed by multiple solid tumors, including 88% of osteosarcomas and 98% of neuroblastomas. However, osteosarcomas are highly heterogeneous, with many tumors exhibiting GD2 expression on <50% of the individual cells, while some tumors are essentially GD2-negative. Anti-GD2 immunotherapy is the current standard of care for high-risk neuroblastoma, but its application to recurrent osteosarcomas, for which no effective therapies exist, has been extremely limited. This is, in part, because the standard assays to measure GD2 expression in these heterogeneous tumors are not quantitative and are subject to tissue availability and sampling bias. To address these limitations, we evaluated a novel, sensitive radiotracer [ Cu]Cu-Bn-NOTA-hu14.18K322A to detect GD2 expression in osteosarcomas (six patient-derived xenografts and one cell line) using positron emission tomography (PET). Tumor uptake of the radiolabeled, humanized anti-GD2 antibody [ Cu]Cu-Bn-NOTA-hu14.18K322A was 7-fold higher in modestly GD2-expressing osteosarcomas (32% GD2-positive cells) than in a GD2-negative tumor (9.8% vs. 1.3% of the injected dose per cc, respectively). This radiotracer also identified lesions as small as 29 mm in a 34% GD2-positive model of metastatic osteosarcoma of the lung. Radiolabeled antibody accumulation in patient-derived xenografts correlated with GD2 expression as measured by flow cytometry (Pearson = 0.88, = 0.01), distinguishing moderately GD2-expressing osteosarcomas (32%-69% GD2-positive cells) from high GD2 expressors (>99%, < 0.05). These results support the utility of GD2 imaging with PET to measure GD2 expression in osteosarcoma and thus maximize the clinical impact of anti-GD2 immunotherapy. SIGNIFICANCE: assessment of all GD2-positive osteosarcoma sites with a novel PET radiotracer could significantly impact anti-GD2 immunotherapy patient selection and enable noninvasive probing of correlations between target expression and therapeutic response.